ENTEROVIRUS INFECTION: VARIETY OF ETIOLOGICAL FACTORS AND CLINICAL MANIFESTATIONS - O. I. Kanaeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. Enteroviruses are widely distributed human infectious pathogens. In spite of infection a disease does not manifest in majority number of cases. However, in some infected persons the different kind of symptoms can be observed; from common cold signs up to  aseptic (serous) meningitis and myocarditis. Severe enteroviral cases with lethal outcomes are rarely reported. Ability of enteroviruses to cause large outbreaks and even epidemic distribution is very significant for health care systems. Taking in account a high genetic diversity of enteroviruses it is possible appearance of new highly pathogenic strains in the future. In some countries including the Russian Federation the permanent surveillance for enteroviral infections is provided besides of WHO polio elimination program. The laboratory diagnostics of enterovirus infections is complicated by numerous of pathogen serotypes. Thus, classical virological methods should be supported by molecular-biological tools to sequence pathogen genome and to define phylogenetic relations between different enterovirus strains.